Transformation of Carbon and Humus in Irrigated Meadow Soils of Deserts - Askarov Khasanboy Kholdorovich (Web of Journals Publishing, 2023)
Accumulation of soil carbonates in the soil profile occurs mainly during the evaporation of mineralized groundwater in the modern hydromorphic stage of soil formation, and not during soil formation. assortment of plant residues. The increase in organic carbon in irrigated soils is associated with an increase in the recency of development and cultivation.
Keywords: pedogen, carbon, lithogen, humus, organic carbon, mineral carbon, conservative, soil cover, accumulation.